DIGITAL HANGMAN GAME TO IMPROVE STUDENT’S VOCABULARY MASTERY IN TEACHING NARRATIVE TEXT - Zaqiyah Lailatul Farihah; Etika Rachmawati (JALL (Journal of Applied Linguistics and Literacy), 2020)
This study aims at investigating the use of digital hangman game to improve students’ vocabulary mastery in teaching narrative text at tenth grade at one of Islamic Senior High School in Padamulya Ciamis, Indonesia. The writers used convergent parallel mixed methods design as a method of the study because the convergent parallel mixed method is a form of mixed-method design in which the researcher converges quantitative and qualitative data in order to provide a comprehensive analysis. Experimental research was used in this study. Moreover, the data in this study were collected from several sources including achievement tests, questionnaires, and observation. The result showed that t-observe was 10.992 and t-critical at df=19 on level 0.05 with a two-tailed test was 2.093, which means that t-critical was less than t-observe and alternative hypotheses were accepted. Thus, the students generally pleased with the teaching narrative text by using the digital hangman game. Furthermore, almost the students gave their good responses to the implementation of the game. For further researchers, it gives broad opportunities in making this study more complete in the same field with a different interest such as how to teach narrative text through other strategies.Keywords: Hangman Game, Vocabulary, Narrative Text